PENGARUH PENDIDIKAN DAN PELATIHAN, PEMBELAJARAN ORGANISASI TERHADAP KINERJA DENGAN KOMPETENSI SEBAGAI MEDIASI - Kunartinah .; Fajar Sukoco (Jurnal Bisnis dan Ekonomi, 2010)
This study aims to examine and analyze the influence of education and training andorganizational learning to competence, the influence of education and training and organizationallearning on performance. and analyze whether the effect of competence can mediate the relationshipof education and training and organizational learning on performance. The population in this studywere junior high school teachers RSBI in Semarang, which amounts to 95 people. Researchinstrument used in testing the validity and reliability. The analysis tool used is multiple regression,hypothesis testing device using t test and mediation. Questionnaire as a means of collecting primarydata, Linkert scale of measurement used by seven (seven) of alternative answers. Secondary dataobtained from institutional documentation. Test results showed that the instrument is valid andreliable research, multiple regression produced a positive unstandardized beta for all variables. Ttest shows there is partially positive and significant influence on the variable-variable diteliti.Ujihypothesis states that the hypothesis was accepted. The results showed that: (1) education andtraining has positive and significant effect on competence (2) organizational learning has positiveand significant effect on competence (3) education and training has positive and significant impacton performance (4) organizational learning has positive and significant impact performance (5)Competence and significant positive effect on performance. (6) Competence is not effective enoughto explain the influence of education and training on performance (7) Competence able to explaineffectively influence organizational learning on performance.Keywords: education and training, organizational learning, competence and performance.PendahuluanMenurut UU No: 20/tahun 2003 tentangSistem Pendidikan Nasional, Pendidikan adalahusaha sadar dan terencana untuk mewujudkansuasana belajar dan proses pembelajaran,agarpeserta didik secara aktif mengembangkanpotensi dirinya untuk memiliki kekuatan spiritualkea gamaan, pengendalian diri, kepribadian,kecerdasan, akhlak mulia, serta ketrampilan yangdiperlukan dirinya, masyarakat, bangsa dannegara. Bab XIV Pasal 50 ayat 3 menyebutkanbahwa “pemerintah daerah harusmengembangkan sekurang-kurangnya satusatuan pendidikan menjadi bertarafinternasional”. Dalam upaya melaksanakan UUtersebut, Dirjen Mandikdasmen menetapkankebijakan untuk mengembangkan SekolahBertaraf Internasional (SBI). Untukmerealisasikan rencana tersebut,maka mulaitahun ajaran 2007/2008 mulaimenyelenggarakan Rintisan Sekolah BertarafInternasional (RSBI) SMP. Hingga tahun 2009Kementerian Diknas sudah mendanai kepada320 SMA, 118 SMK, 300 SMP dan 136 SD yangtersebar di 481 kabupaten/kota diseluruhIndonesia. Evaluasi akan dilaksanakan padatahun 2010/2011 karena pemberian dana bantuanuntuk SMP selama 4 (empat) tahun.Untuktingkat SMP, dana bantuan setiap sekolah Rp.400 juta pada tahun 2007 dan Rp. 300 juta padatahun 2008-2010.Menurut Mendiknas evaluasi RSBI akandilakukan secara menyeluruh dan melihat apakahsemua ketentuan telah dipenuhi, seandainyaRSBI tidak mencapai target yang telahditentukan, sangat mungkin RSBI akandikembalikan statusnya menjadi sekolah regular.Sebaliknya,jika telah terpenuhi akan langsung